MEDIATION AS AN ALTERNATIVE DISPUTE RESOLUTION: CUSTOMARY LAW PERSPECTIVE - Taufik Siregar; Anwar Sadat Harap; Ikhsan Lubis (Kanun Jurnal Ilmu Hukum, 2022)
The goal of this research is to describe mediation as an alternative technique of conflict settlement under customary law, in both criminal and civil matters. Dispute resolution processes based on customary law play an important role in decreasing litigation. Mediation is a cornerstone of traditional law-based dispute settlement. This study uses descriptive qualitative research to better understand the phenomenon of mediation as an alternative form of conflict settlement under customary law. The data was gathered through a literature review and document analysis. The technique of data analysis employed in this study was a qualitative descriptive technique based on Miles and Huberman's interactive model. The findings reveal that mediation aids indigenous people in three ways: (i) maintaining ownership of conflicts; (ii) utilizing parts of customary law and practice; and (iii) finding a solution that is consistent with their cultural values. Furthermore, it appears that in traditional civilizations, mediators strive to guarantee that "peace and harmony prevail in society" because of the agreement. As a result, people who still adhere to customary law may employ customary law mediation as an alternate means of settling problems